Efektivitas Penggunaan Aplikasi Kahoot berbasis Problem Based Learning Terhadap Hasil Belajar Geografi Siswa Kelas X SMA Negeri 2 Bantul Tahun Ajaran 2021/2022 - Rahayu Okta Viani; Sugiyanto Sugiyanto; Lintang Ronggowulan (Universitas Sebelas Maret (UNS), 2025)
This study aims to: (1) analyze the differences in student learning outcomes between the use of Google Form with the lecture and question and answer method, the use of Kahoot with the same method, and the use of Kahoot through a problem-based learning model in class X students of SMA Negeri 2 Bantul; (2) determine the learning outcomes of students who use Kahoot and Google Form through the lecture and question and answer method; and (3) compare the learning outcomes of students who utilize Kahoot through problem-based learning with the lecture and question and answer method. The study used a quasi-experimental design. The results showed that: (1) there were differences in learning outcomes between the three treatments, with a significance of 0.000 < 0.05 so that H0 was rejected; (2) Kahoot through the lecture and question and answer method was more effective than Google Form, as evidenced by a significance value of 0.023 < 0.05; and (3) Kahoot with a problem-based learning model was more effective than the lecture and question and answer method, with a significance value of 0.006 < 0.05.